IMPLEMENTASI PASAL 35 AYAT 1 HURUF C PERATURAN KAPOLRI NOMOR 9 TAHUN 2012 TENTANG SURAT IZIN MENGEMUDI BAGI DISABILITAS DAKSA - Hizbillah, Sultan Taqiyuddin; Nugroho, Widhi Cahyo (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
A person with disability is given special regulation regarding the acquisition of driver's licence (driver's license) d for those who are handicapped in driving traffic. The study aims to find out how section 35 verses (Lala 1234)1 letter c works the 2012 sheriff's rule number 9 on driver's license for disability. In practicee there are still obstacles andoobstacles in the processoof obtaining the driver's license d, so someoof them stillodo not have the d's licenseoto drive. The goal to beoachieved in thisostudy is: 1) to know the application of article 35 verse 1 letter c of the 2012 chief's law no. 9 on the driver's license for disabilities. 2) to know the physical criteria applied to those with disabilities to have a driver's licence. Thisotype of study can be classified as normatization studies because through legislation approaches and study on disability behaviors gained driver's license D and obstaclesoin the process. Theoresearch site is at stone city p.d. Data collecting uses a technique interview with informants related to the research being researched. Further data results in qualitative analysis to provide exposure to research. Theodata analysis used by the writer as a qualitative descriptiveomethod is aodescription in the regular,o coherent, logical, and effectivee form of sentences. Based on the results of studies, section 35 clause 1 letter c of the 2012 chief's rule no. 9 on driver's license is still underwriting because of some obstacle factor, oneoof which is theolack of knowledge of theo perpetrators of the traffic rule.